New instrument for effective detection of a history of COPD exacerbations, including usually unreported events - Zatloukal, Jaromir; Volakova, Eva; Kovacikova, Jana; Kulirova, Martina; Maruscak, Miroslav; Hytychova, Blanka; Koblizek, Vladimir (Frontiers in medicine, 2025)
BACKGROUND: COPD exacerbations are important events for disease management. The incidence of exacerbations impacts prognosis, guides treatment, and predicts future exacerbations. Despite their importance, exacerbations are often underdiagnosed and underreported. The aim of our study was to test and evaluate the effectiveness of a structured checklist for detecting past exacerbations that we developed and that would be suitable for routine clinical practice. METHODS: 350 patients with COPD and FEV1 < 80% of the predicted value were enrolled in 35 centers. Each patient completed a structured checklist and underwent an interview with the physician. The number of exacerbations, their symptoms and duration, and the treatments were evaluated. Clinical data on exacerbations in the previous 12 months were retrieved from the patient's medical records and analyzed retrospectively. The data obtained using the structured checklist were compared with the data from the interviews and medical records. RESULTS: Compared to the patient-physician interview, the structured checklist detected more exacerbations since the previous visit (p = 0.025). The difference was significant also for severe exacerbations (p = 0.003). In patients reporting only one event, the structured checklist was more sensitive in detecting mild events than the interview (p < 0.001). The structured checklist detected mild exacerbations in 10 patients in whom the interview detected none. Compared to the number of exacerbations in the medical records, the structured checklist detected more than twice as many events. The mean duration of an exacerbation was 9.7 days, and the most prominent symptoms were dyspnea and productive cough. CONCLUSION: Proposed structured checklist improved the detection of past exacerbations, including usually unreported events. Moreover, the structured checklist allows the severity and other clinical characteristics of past exacerbations to be specified and used to direct further COPD therapy.
Keywords: disease history; questionnaire; dyspnea; structured checklist; cough; obstructive lung disease; flare-up